1999
DOI: 10.1007/s002130050951
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aggressive behavior during withdrawal from long-term marijuana use

Abstract: Our findings confirm previous reports of an abstinence syndrome associated with chronic marijuana use and suggest that aggressive behavior should be an additional component of this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(80 citation statements)
references
References 34 publications
4
71
0
5
Order By: Relevance
“…Nonetheless, clinicians have described the syndrome as one characterized by restlessness, anorexia, irritability, and insomnia and noted that it can last as long as 1 week to 10 days (Budney, Novy, & Hughes, 1999;Haney et al, 1999). One study recently demonstrated, using a laboratory measure of aggression, that long-term THC users, tested 3 and 7 days into abstinence, were significantly more aggressive than controls, their own preabstinence behavior, as well as their own behavior at Day 28 of abstinence (Kouri, Pope, & Lukas, 1999). Thus, it may well be the case that the greatest risk of violence from a user of THC is within the first week of an acute period of abstinence.…”
Section: Cannabismentioning
confidence: 99%
“…Nonetheless, clinicians have described the syndrome as one characterized by restlessness, anorexia, irritability, and insomnia and noted that it can last as long as 1 week to 10 days (Budney, Novy, & Hughes, 1999;Haney et al, 1999). One study recently demonstrated, using a laboratory measure of aggression, that long-term THC users, tested 3 and 7 days into abstinence, were significantly more aggressive than controls, their own preabstinence behavior, as well as their own behavior at Day 28 of abstinence (Kouri, Pope, & Lukas, 1999). Thus, it may well be the case that the greatest risk of violence from a user of THC is within the first week of an acute period of abstinence.…”
Section: Cannabismentioning
confidence: 99%
“…Analogous results were obtained in the ultrasonic vocalization emission test, which measures the number of stress-induced vocalizations emitted by rat pups removed from their nest . If confirmed in further behavioral models, these findings would suggest that inhibition of intracellular FAAH activity might offer an innovative target for the treatment of anxiety , which is also a feature of marijuana withdrawal (Kouri et al, 1999;Kouri and Pope, 2000;Budney et al, 2003).…”
Section: Behavioral Effects Of Faah Inhibitorsmentioning
confidence: 82%
“…The latter consists of a constellation of symptoms similar to those seen with nicotine withdrawal, which include irritability, sleep difficulty, decreased appetite, weight loss, and increased anger and irritability (Kouri et al, 1999;Kouri and Pope, 2000;Budney et al, 2003). There have been few pharmacological attempts to alleviate this syndrome (McRae et al, 2003), but one approach using oral D 9 -THC has recently shown significant promise (Haney et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in the ultrasonic vocalization emission test, which measures the number of stress-induced vocalizations emitted by rat pups removed from their nest. These results suggest that inhibition of intracellular FAAH activity may offer an innovative target for the treatment of anxiety [126], which is also a feature of marijuana withdrawal [50,51,127]. Forebrain sites that might be implicated in such actions include the basolateral amygdala, the anterior cingulate cortex and the prefrontal cortex, all key elements of an 'emotion circuit' that contains high densities of CB1 receptors [18,19].…”
Section: Stress and Anxietymentioning
confidence: 99%